2022
DOI: 10.1007/s12325-022-02235-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review with Meta-Analysis: Efficacy and Safety of Lusutrombopag for Severe Thrombocytopenia in Patients with Chronic Liver Disease Undergoing Invasive Procedures

Abstract: Introduction: Lusutrombopag is an oral thrombopoietin receptor agonist (TPO-RA). Clinical trials have shown lusutrombopag's efficacy in reducing need for preoperative platelet transfusion in patients with chronic liver disease (CLD) and severe thrombocytopenia. This analysis assessed efficacy and safety of lusutrombopag in patients with severe throm-bocytopenia and CLD undergoing planned invasive procedures. Methods: An electronic database search (through 1 December 2020) identified three randomised, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Similarly, a systematic meta-analysis performed by Orme et al [ 27 ] showed the efficacy and safety of treatment with lusutrombopag in this patient population. More patients treated with lusutrombopag (compared to placebo) required no platelet transfusion and no rescue therapy for bleeding for at least 7 days post-procedure (RR 3.42; 95%CI: 1.86, 6.26; P = 0.0001).…”
Section: Introductionmentioning
confidence: 66%
“…Similarly, a systematic meta-analysis performed by Orme et al [ 27 ] showed the efficacy and safety of treatment with lusutrombopag in this patient population. More patients treated with lusutrombopag (compared to placebo) required no platelet transfusion and no rescue therapy for bleeding for at least 7 days post-procedure (RR 3.42; 95%CI: 1.86, 6.26; P = 0.0001).…”
Section: Introductionmentioning
confidence: 66%
“…Unlike ITP, which has been the clinical indication of nearly all TPO-RAs in the market, only lusutrombopag [ 14 , 15 ] and avatrombopag [ 16 ] have been approved for the treatment of thrombocytopenia in adult CLD patients scheduled to invasive procedures. A pharmacoeconomic study [ 40 ], and a systematic review and meta-analysis [ 41 ] have shown that the use of TPO-RAs could lower the bleeding risk, reduce platelet transfusions and be more cost-effective in CLD patients undergoing medical procedures. Notably, eltrombopag has an FDA black box warning of hepatotoxicity and has been reported to cause venous thromboembolism in CLD patients [ 42 ], hence, it has been suggested that eltrombopag should not indicated in CLD-related thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet transfusions have limited effects in patients with HCV cirrhosis and thrombocytopenia, with platelet counts increasing only 20% after transfusion [ 19 ]. Cirrhotic patients with thrombocytopenia have been treated with thrombopoietin (TPO) receptor agonists such as lusutrombopag a few weeks before invasive procedures [ 19 , 20 ], markedly reducing the need for platelet transfusion. Although several weeks are required for DAA to increase platelet counts, the effects of HCV eradication by DAA are comparable to those of platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%